Ijȃrah Muntahiyah Bi al-Tamlȋk: Sebuah Alternatif Pemberdayaan Tanah Wakaf - Iza Hanifuddin; Sunan Autad Sarjana (Muslim Heritage, 2018)
Abstract: Indonesia has a very extensive waqf land. Every year is always increasing. Size donated land is a great potential for the public welfare if managed with productive and professional. However, the institution of waqf as nȃdhir often find it difficult to finance the development and management of the donated land. This article is a literature review that aims to seek an alternative agreement that can be used to empower the donated land. The results showed that much of the literature of jurisprudence has defined-contract agreement for the empowerment of waqf land. Among the contract is ijȃrah classifiedtraditional ceremony in the empowerment of waqf land. Therefore, more advanced economic system, then the contract development experience and innovation to be ijȃrah muntahiyah bial-Tamlik.This contract helped nȃdhir in financing to empower the donated land. Because all costs empowerment of financiers, and after completion of the contract, the investor will transfer ownership of the building to nȃdhir.Abstrak: Indonesia memiliki tanah wakaf yang sangat luas. Setiap tahunnya senantiasa mengalami peningkatan. Luas tanah wakaf ini merupakan potensi besar untuk mewujudkan kesejahteraan masyarakat jika dikelola dengan produktif dan profesional. Akan tetapi, lembaga wakaf sebagai nȃdhir seringkali mendapatkan kesulitan untuk membiayai pengembangan dan pengelolaan tanah wakaf tersebut. Artikel ini merupakan kajian pustaka yang bertujuan untuk mencari akad alternatif yang bisa digunakan dalam memberdayakan tanah wakaf.  Hasil kajian menunjukkan bahwa banyak literatur fikih telah menentukan akad-akad untuk pemberdayaan tanah wakaf. Di antara akad tersebut adalah ijȃrah yang tergolong akad tradisional dalam pemberdayaan tanah wakaf. Oleh karena sistem perekonomian yang semakin maju, maka akad tersebut mengalami pengembangan dan inovasi hingga menjadi ijȃrah muntahiyah bi al-tamlîk. Akad ini banyak membantu nȃdhir dalam pembiayaan untuk memberdayakan tanah wakaf. Karena semua biaya pemberdayaan dari pemodal, dan setelah selesai akad, pemodal akan mengalihkan kepemilikan bangunan kepada nȃdhir.